Exploring a mobile application for reporting non-compliance with halal standards: A pilot study - Mohamad Reeduan, Mustapha; Noridayu, Mah Hashim; Adam, Anwar (Universiti Malaysia Pahang Al-Sultan Abdullah, 2024)
The purpose of this paper is to explore a mobile application for Halal Reporting Non-Compliance. The app is developed to enable users to report non-compliance with the Halal standards and encourage community involvement in promoting Halalan Tayyiban, as well as providing information and education on Halal issues. The project’s objectives include creating a user-friendly app for reporting Halal non-compliance, fostering transparency in the Halal industry, and educating consumers about Halal standards, certification, and compliance. To achieve these objectives, market research methods were chosen in order to assess the viability and value of developing a mobile application. A cross-sectional design using questionnaires was conducted as a pilot study to potential users between May and June 2023. Sixty-eight students participated in this survey. Regarding the most important factors that respondents consider in choosing a mobile application, 48 (70.6%) consider the accuracy of information and trustworthiness of the reporting system as the most important factor when choosing a mobile application that promotes Halal compliance and enables reporting of non-compliance with Halal standards. This initial research serves as a promising foundation for future development of the Halal Report app, with a clear understanding of user expectations and preferences.